Implikasi Percakapan dalam Film James Bond: Skyfall - Ariyanto, Joko; Yulianto, Yulianto; Roziah, Roziah; Agnesia, Dwita; Irenta, Astrid (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study examines the use of conversational implications in Skyfall (2012) through pragmatic analysis based on Grice's Principle of Cooperation. This study aims to identify how maximal violations contribute to implicit meaning and character development in cinematic dialogue. A qualitative descriptive method was used, focusing on 25 dialogue snippets selected through targeted sampling based on their relevance to the implications. The data was collected by watching the movie repeatedly, transcribing key interactions, and encoding each utterance according to the four conversation maxims Quantity, Quality, Relationship, and How. Analytical procedures involve (1) identifying potential implications, (2) determining the maxims that are being violated or adhered to, (3) interpreting the implied meanings using contextual and theoretical cues, and (4) categorizing the communicative functions of each implication. The findings show that the Maxim of Relations is most often violated, followed by Quantity, Quality, and Manner, which shows the dominance of impurity, sarcasm, and relevance-based inference. Such implications have a variety of pragmatic functions, including sarcasm, emotional concealment, seduction, power negotiation, and indirect threats. These patterns highlight how Skyfall builds James Bond's communicative persona strategic, emotionally controlled, and dependent on implications rather than explicit. The study concludes that implication is a central feature of film discourse, which enriches the depth of narrative and character interaction, while demonstrating the value of pragmatic analysis in understanding cinematic storytelling.